Education, gender and cohort fertility in the Nordic countries - Jalovaara Marika; Neyer Gerda; Andersson Gunnar; Dahlberg Johan; Dommermuth Lars; Fallesen Peter; Lappegård Trude (Springer, 2025)
Systematic comparisons of fertility developments based on education, gender and country context are rare. Using harmonized register data, we compare cohort total fertility and ultimate childlessness by gender and educational attainment for cohorts born beginning in 1940 in four Nordic countries. Cohort fertility (CTF) initially declined in all four countries, although for cohorts born in the 1950s and later, the CTF remained stable or declined only modestly. Childlessness, which had been increasing, has plateaued in Denmark, Norway and Sweden. Women’s negative educational gradient in relation to total fertility has vanished, except in Finland, while men’s positive gradient has persisted. The highest level of men’s childlessness appears among the least educated. In the oldest female cohorts, childlessness was highest among the highly educated, but these patterns have changed over the cohorts as childlessness has increased among the low educated and remained relatively stable among higher educated women. In Denmark, Norway and Sweden, childlessness is now highest among the least educated women. We witness both a new gender similarity and persistent (among men) and new (among women) educational disparities in childbearing outcomes in the Nordic region. Overall, the number of low educated has decreased remarkably over time. These population segments face increasing social and economic disadvantages that are reflected as well in their patterns of family formation.